Bismuth telluride–copper telluride nanocomposites from heterostructured building blocks. Issue 40 (30th September 2020) - Zhang, Yu; Liu, Yu; Calcabrini, Mariano; Xing, Congcong; Han, Xu; Arbiol, Jordi; Cadavid, Doris; Ibáñez, Maria; Cabot, Andreu
Abstract : Appropriately designed Bi2 Te3 –Cu2− x Te nanocomposites allow an improvement of over 50% of the thermoelectric figure of merit of Bi2 Te3 . Abstract : Appropriately designed nanocomposites allow improving the thermoelectric performance by several mechanisms, including phonon scattering, modulation doping and energy filtering, while additionally promoting better mechanical properties than those of crystalline materials. Here, a strategy for producing Bi2 Te3 –Cu2− x Te nanocomposites based on the consolidation of heterostructured nanoparticles is described and the thermoelectric properties of the obtained materials are investigated. We first detail a two-step solution-based process to produce Bi2 Te3 –Cu2− x Te heteronanostructures, based on the growth of Cu2− x Te nanocrystals on the surface of Bi2 Te3 nanowires. We characterize the structural and chemical properties of the synthesized nanostructures and of the nanocomposites produced by hot-pressing the particles at moderate temperatures. Besides, the transport properties of the nanocomposites are investigated as a function of the amount of Cu introduced. Overall, the presence of Cu decreases the material thermal conductivity through promotion of phonon scattering, modulates the charge carrier concentration through electron spillover, and increases the Seebeck coefficient through filtering of charge carriers at energy barriers. These effects result in an improvement of over 50% of the thermoelectric figure of merit of Bi2 Te3 .